Humanitarian assistance in the Asia-Pacific during COVID-19 - Chen, Christopher Zhiming (Nanyang Technological University, 2020)
As the world grapples with the COVID-19 pandemic, the threat of natural hazards still looms large. How will humanitarian response to a major natural hazard be affected during the COVID-19 pandemic? As the monsoon season begins in the Asia-Pacific, particularly in the South West Pacific and Southeast Asia, this is a scenario that countries face. The overlapping effects of a pandemic and a natural hazard can compound socio-economic vulnerabilities in countries. While the current focus is on managing the COVID-19 pandemic, governments and communities also need to be prepared for concurrent natural hazards. This NTS Insight explores the effects of concurrent pandemic-disaster events, and how they threaten states and societies in the Asia-Pacific. This Insight demonstrates the potential challenges of dual crises on societies and vulnerable populations. It argues that the current situation calls for a broader and deeper localisation of the humanitarian system, one that places human security as its core organising principle unlike the backseat it currently takes today. To this end, it argues that inter-regional cooperation can further localisation through the experience of the South West Pacific where human security is articulated as national security and the cooperation in Southeast Asia on disaster response which builds national capacity. With overseas travel and supply chain restrictions severely hampering the movement of relief items and international humanitarian workers, the need to empower and strengthen local humanitarian actors becomes even more pressing.